From Peaceful Protest to Bloodbath: An Interrogation of the Link between the #EndSARS Protest and Policing Strategies in Nigeria - Irene, Oseremen Felix (ABUAD Journal of Social and Management Sciences, 2023)
The #EndSARS protest by the Nigerian youths was against police brutality. It started peacefully but ended in violence and bloodbath. This study investigates the link between the #EndSARS protest and policing strategies in Nigeria. Structured questionnaires were used to collect primary data from 194 randomly selected respondents from a population of Police officers. Secondary data was sourced from library materials such as textbooks, journals, newspapers and websites. SPSS was used to analyse the primary data collected for the study. Findings from the study revealed that there is a significant relationship between the #EndSARS protest and policing strategies in Nigeria. The study therefore suggests people friendly policing strategies that would promote effective civil-police relationship and collaboration in the country.